THE EXPLORATION OF NUMEROUS DIMENSIONS OF SNIGDHA AND RUKSHA GUNA – A LITERATURE REVIEW (AYUSHDHARA, 2020)
The Srushti, Sthiti and Laya of entire universe is under the control of Snigdha and Ruksha guna. Srushtiutpatthi is because of Ruksha and Snigdha guna together. Sthithi is because of the predominance of Snigdha guna and Laya is because of predominance of Ruksha guna. The entire universe is balanced by their equal participation. Based on Loka Purusha Samya Siddhanta, these Gunas in Dravya as well as in Shareera has to be understood and subsequently utilized. Because, Guna is in inseparable relation with Dravya and Dravya imparts Guna in Shareera. Hence the main Aim of the study is to compile and analyze the physiological pathological and therapeutical aspects of Snigdha and Ruksha guna individually and validate their combined effect based on the concept- Pravruttirubhaysyatu.